Taxonomic revision of Eurotium and transfer of species to Aspergillus - Hubka, Vit; Kolarík, Miroslav; Kubátová, Alena; Peterson, Stephen W (Mycologia, 2013)
Aspergillus section Aspergillus contains economically important, xerophilic fungi that are widely distributed in nature and the human environment and are known for their ability to grow on substrates with low water activity. The taxa were revised based on sequence data from four loci, PCR fingerprinting, micro- and macromorphology, and physiology. The number of taxa was reduced to 17 species, all of which can be distinguished with sequence data from either the caM or RPB2 locus. The original description of A. proliferans was supplemented by a description of its teleomorph. This species seems to be relatively common and often has been confused with A. glaucus. In addition, green sporulating isolates of A. niveoglaucus isolated from food and several other substrates are indistinguishable in phenotype from A. glaucus. A dichotomous key based on ascospore size and ornamentation and the ability to grow at specific combinations of temperature and water activity is provided for identification of species. In response to recent changes in the botanical code, we transferred the Eurotium species to Aspergillus and selected one name for each species.
Keywords: Terminology as Topic; multilocus sequence typing; food spoilage; Ecosystem; stored grain; low water activity; ekosystém; Sequence Analysis, DNA; scanning electron microscopy; xerophilic species; Eurotium; sekvenční analýza DNA; Aspergillus; terminologie jako téma